(3CNHGQ GdLfs - (3jhSa, YUGes ((3GdLjRI (B[(3eUQ(B]s (3OGQ WjHI ddWHGYIs, 2015)
(3GdcJGH jJfGhd ehVhY GdLf hCfhGYg hYdGbI GdEfSGf HbQjfg hcja jbi GdEfSGf faSg ef NWQ GdLf hcja cGf jYGdL GdQShd GdcQje GdSMQ ceG jJfGhd GdcJGH MhGQ GdCfHjGA hGdUMGHI eY GdLfs
(3GdeMJhjGJ (B: (3eG gh GdLf(B--(3COdI hLhO GdLf(B--(3CfhGY GdLf(B--(3GdbQjf hYdGbJg HdEfSGf(B--(3ai CMhGd GdLf(B--(3YdGL GdeUQhY ef cJGH GdWH GdfHhis
11
Keywords: (3GdJYGhjPs; (3GdLfs; (3GdNQGaGJs; (3GdSMQs; (3GdTjGWjf hGdLfs; (3GdWdGSes; (3GdYdGL GdOjfjs; (3GdYdGL HGdbQCfs; (3Gdbhi GdNajIs